Is Nitrogen a Key Determinant of Water Transport and Photosynthesis in Higher Plants Upon Drought Stress? - Ding, Lei; Lu, Zhifeng; Gao, Limin; Guo, Shiwei; Shen, Qirong (Frontiers in Plant Science, 2018)
Drought stress is a worldwide issue in agricultural production. Plants respond to drought stress via a series change of physiological, cellular and molecular processes for survival. The regulation of water transport and photosynthesis plays crucial role in improving plants drought tolerance. Nitrogen (N, ammonium and nitrate) is an essential macro-nutrient for plant, and it could affect many aspects of plant growth and metabolic pathway, including water relations and photosynthesis. This review focus on that water transport and photosynthesis are affected by drought stress, including the regulation of hydraulic conductance, aquaporin expression and photosynthesis. It`s reviewed that the cross talk of nitrogen, water transport and drought stress in higher plants.